Analysis of risk factors, pathogenic bacteria of maternal sepsis in term pregnant women with positive blood culture during hospitalization. Issue 7 (19th February 2021) - Wen, Yanqing; Chen, Hong; Ming, Xin; Chen, Xiaoyan; Zhou, Wei
Abstract : Abstract: The objective of this study was to evaluate the risk factors, pathogenic bacteria and drug sensitivity of maternal sepsis, and provide evidence for clinical prevention and treatment. A retrospective investigation of pregnant women with full-term maternal sepsis was performed to analyze the risk factors, pathogenic bacteria, and drug sensitivity of maternal sepsis. Univariate analysis showed that temperature, serum procalcitonin (PCT) and C-reactive protein (CRP) at admission, white blood cell count (WBC), PCT, CRP and neutrophilic granulocyte percentage (N%) during fever, premature rupture of membranes (PROM), antibiotic use within 1 week, mode of production, onset and duration of fever, between groups were statistically significant ( P  < .05). Logistic regression analysis showed that cesarean section was an independent risk factor for sepsis (OR = 11.839, 95%CI: 3.121–44.906). Apparent increase was found in body temperature (OR = 3.664, 95%CI: 1.722–7.795), duration of fever (OR = 1.953, 95%CI: 1.242–3.071), and PCT (OR = 1.080, 95%CI: 1.002–1.163). Also, increasing neutrophil ratio (OR = 1.180, 95%CI: 1.073–1.297) indicated a high possibility of maternal sepsis. The organism Escherichia coli ( E. coli ) was the most common pathogenic bacteria in the positive blood culture group (90%), and the sensitivity to carbapenems (meropenem and imipenem/cilastatin) was 100%, that to piperacillin-tazobactam and amoxicillin sulbactam was over 90%, and that to ceftazidime was 95%. Cesarean section was an independent risk factor for maternal sepsis in term pregnant women with positive blood culture. Besides, the E . coli was the most common pathogenic bacteria in the positive blood culture group. Antibiotics should be used in time and reasonably when the temperature was significantly increased with elevated PCT and N% after a cesarean section.